Limb Remote Ischemic Conditioning: Mechanisms, Anesthetics, and the Potential for Expanding Therapeutic Options - Chen, Gangling; Thakkar, Mrugesh; Robinson, Christopher; Doré, Sylvain (Frontiers in Neurology, 2018)
Novel and innovative approaches are essential in developing new treatments and improving clinical outcomes in patients with ischemic stroke. Remote ischemic conditioning (RIC) is a series of mechanical interruptions in blood flow of a distal organ, following end organ reperfusion, shown to significantly reduce infarct size through inhibition of oxidation and inflammation. Ischemia/reperfusion is what ultimately leads to the irreversible brain damage and clinical picture seen in stroke patients. There have been several reports and reviews about the potential of RIC in acute ischemic stroke; however, to focus here is a comprehensive look at the differences in the three types of RIC (remote pre-, per-, and postconditioning). There are some limited uses of preconditioning in acute ischemic stroke due to the unpredictability of the ischemic event; however, it does provide the identification of biomarkers for clinical studies. Remote limb per- and postconditioning offer a more promising treatment in the clinical setting as they can be harnessed during or after the initial ischemic insult. Though further research is needed, it is imperative to discuss the importance of preclinical data in understanding the methods and mechanisms involved in RIC. This understanding will facilitate translation to a clinically feasible paradigm for use in the hospital setting.